2015
DOI: 10.1080/13501763.2015.1008792
|View full text |Cite
|
Sign up to set email alerts
|

Legislative lobbying in context: towards a conceptual framework of interest group lobbying in the European Union

Abstract: We outline a conceptual framework that identifies and characterizes the contextual nature of interest group politics in the European Union (EU) to better understand variation in interest group mobilization, lobbying strategies and interest group influence. We focus on two sets of contextual factors that affect EU interest group lobbying. First, we argue that interest group activities are shaped by several policy-related factors, namely the complexity, the policy type, the status quo, the salience and the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 59 publications
(85 reference statements)
4
79
0
6
Order By: Relevance
“…While such theorizing is becoming increasingly accepted in EU studies, some scholars argue that increased salience can actually create room for governments to exercise their own prerogatives by choosing between those business group interests that best fit the state's goals (Woll, 2013). Others assert that increased salience, while brewing conflict, inevitably privileges the voices of the largest coalitions (Klüver et al, 2015a). Salience can have differential impacts on the business communitywith smaller, nationally oriented firms that are seen as more legitimate defeating their transnational 'big business' counterparts (Keller, 2016).…”
Section: Issue Salience and …mentioning
confidence: 99%
“…While such theorizing is becoming increasingly accepted in EU studies, some scholars argue that increased salience can actually create room for governments to exercise their own prerogatives by choosing between those business group interests that best fit the state's goals (Woll, 2013). Others assert that increased salience, while brewing conflict, inevitably privileges the voices of the largest coalitions (Klüver et al, 2015a). Salience can have differential impacts on the business communitywith smaller, nationally oriented firms that are seen as more legitimate defeating their transnational 'big business' counterparts (Keller, 2016).…”
Section: Issue Salience and …mentioning
confidence: 99%
“…By residual opportunities we refer to the unregulated administrative space created by selective and incomplete implementation, which either leaves existing political strategies unaffected or permits tobacco companies to adapt their strategies to take advantage of gaps in implementation (hereafter opportunities for policy influence unless stated otherwise). This assumption reflects a finding common to both the political science and public health literatures: corporations select political strategies with reference to the institutional and policy contexts in which they operate [2531]. We seek to map the potential for opportunities for policy influence against a conceptual framework developed from studies on venue shopping [32–36], and corporate political activity based primarily on analyses of internal tobacco industry documents [16, 17].…”
Section: Conceptual Approachmentioning
confidence: 99%
“…The third form, national structural and sectoral interests and their influence on EU politics has been theorized by scholars such as Scharpf (), Moravcsik () and Kohler‐Koch (). Empirically, the influence of national sectoral interests on voting behaviour in the Council has not yet been evaluated comprehensively, despite the vast literature on lobbying activities in the European Union, which, however, have mainly studied the institutional contexts of the Commission and the European Parliament (for an overview, see Klüver et al, ). Concerning the influence of structural interests, some evidence may be contained in the early studies that identified a north–south division between Member States (Kaeding and Selck, ; Mattila, ; Zimmer et al, ).…”
Section: Ministers' Responsiveness To Constituency Interestsmentioning
confidence: 99%